Theoretical and methodological approaches in the study of the phenomenon of cultural heritage (Journal of Philosophy Culture and Political Science, 2018)
In the article the author analyzes the theoretical-conceptual and philosophical-methodological approaches to the phenomenon of cultural heritage. The author of the article considers the main directions of research of the problems of cultural heritage written by domestic scientists. Analyzing the essence and history of the problem of cultural heritage, the author notes that the modern interpretation of this problem was developing gradually. Firstly the essence of the cultural heritage was considered within the framework of the concept of a common culture, Western philosophers made a significant contribution to the study of the concept of cultural heritage. Cultural heritage has been defined as an object of cultural property in the modern conceptual approaches. In the article the author carries out a lexical-semantic analysis of the term “cultural heritage”. In the view of author, many Russian and Western scientists distinguish the following types of cultural heritage: natural objects that have only aesthetic features; According to the author, the theoretical methodological basis for the study of cultural heritage’s problem is axiological approach. Using this approach, the author proposes a framework of cultural heritage: cultural values, cultural traditions and cultural wealth. In the article the author gives a description of the components of the cultural heritage and determines their role on the example of Kazakh people’s culture.Key words: cultural heritage, value, cultural traditions, tradition, cultural wealth, continuity, Kazakh culture.